Endoscopic Endonasal Transodontoid Treatment of a Ruptured Anterior Spinal Artery Aneurysm - Kulubya, Edwin S.; Karnati, Tejas; Thaci, Bart; Cua, David; Duong, Huy (Journal of Neurological Surgery Reports, 2022)
Isolated spinal artery aneurysms are a rare cause of intracranial subarachnoid hemorrhage (SAH). A 49-year-old female presented with severe headache. Initial imaging showed SAH and intraventricular hemorrhage (IVH), but no clear source of bleeding was identified. One week into being observed in the intensive care unit, she reported another severe headache. Computed tomography head showed more SAH and IVH. A second angiogram revealed a ruptured small anterior spinal artery (ASA) aneurysm at the craniocervical junction. She underwent a C1–2 fusion followed by an endoscopic endonasal transodontoid approach and wrapping of the ASA aneurysm. At 2 years' follow-up, there was no sign of aneurysm growth or rerupture. This is the first reported case of an endoscopic endonasal transodontoid approach to an aneurysm.
Keywords: anterior spinal artery aneurysm; endoscopic endonasal transodontoid